Analysis and Optimization of the Start-up Process based on Badaling Solar Power Tower Plant. (May 2015) - Yang, Y.; Wang, Z.; Xu, E.; Ma, G.; An, Q.
Abstract: As the mutual movement of the sun and the earth cause alternating night and day, solar power tower plants face frequently start and stop operations for solar radiation being its energy source. Besides, in the start and stop process of solar tower power plants, key components such as receivers, drum and turbine face rapid changes in temperature and pressure. Therefore, how to select and set reasonable start-up parameters, reducing start-up time was crucial to improve operating efficiency and ensure the operational life of the solar tower power plants. In this paper, how to determine the temperature rising curve of water in the drum during the start-up process was studied. The range of thermal stress and cyclic stress of the drum during start-up were calculated. Genetic algorithms were used to optimize the start-up operation. According to the design parameters of Badaling solar power tower plant, after optimization, the start-up time of the drum was 55 min while the origin time was 120 min. Moreover, it is obvious that the higher rated parameters are, such as rated temperature of the drum, the better is the effect of the optimization methods.